Cobrança de água : uma nova fiscalidade? : os (des)caminhos da tributação ambiental - Campos, Luciana Ribeiro (2006)
We initiate by making a brief summary concerning the importance of water resources and its multiple uses, informing of the environmental crisis. Afterwards the international and national Statutes about water resources are situated historically. A new view of the Constitutional Law in the competency aspect is proposed in the water resource field. It is defined that the access to water resources are a fundamental right. The management of the water is, in itself, a restriction to fundamental rights. Restrictions to fundamental rights are only viable to introduce in the jurisdictional system by means of a Legislative Act. To price the water resource as did the Water Act implies in the establishment of a restriction to fundamental rights, witch can only be legitimated if it is instituted by a Legislative Act. The polluter-pays principle informs the necessity of preservation of water resources. This principle, the fundamental rights theory, the public goods and externalities theory, the Pareto Law and the enlargement of the anthropocentrism are legitimate arguments that sustains the environment taxation. The price of water resource established in the Water Act is a tax, because all the elements in legal definition of a tax are present. The price of water resource established in the Water Act is qualified as a tax to intervene in the economical domain (species of Brazilian taxes). All the aspects in tax instituted in Water Act are identified.